Teacher's Efforts to Improve Elementary Students' Understanding of the Value of Truth in the Qur'an - Didi Maslan; Salminawati Salminawati; Parentah Lubis; Zulham Lubis; Nelly Rahmita (Jurnal Basicedu, 2023)
Teaching the truth is a principal matter that must be given to children from an elementary age. Because, children will easily actualize the value of truth if it is imprinted from the foundation. This study aims to describe the efforts of teachers in increasing the understanding of elementary students aged 6-12 years about the concepts of Islamic teachings including bayani, 'irfani, and burhani. Of course, this theory of truth will be compared between the truth from Western and Islamic perspectives. This research uses a qualitative approach with the method of literature study. Obtaining and analyzing data comes from literature review materials in the form of books, scientific articles, proceedings, and final assignments (thesis, thesis, dissertation). Research data analysis materials were obtained from credible websites such as Google Scholar and Sinta. The results of this study concluded that the teacher's efforts to increase elementary-age students' understanding of bayani, 'irfani and burhani as basic concepts of truth from an Islamic perspective were carried out well. This is based on (1) mainstreaming truth based on revelation/al-Qur'an (the word of Allah swt.) as the highest authority in measuring truth. Then (2) logic in the form of reason, empirical and intuition becomes a supporting factor for students in understanding the truth of Divine words.